2014
DOI: 10.1111/are.12634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietaryNutrafito Pluson growth, haemotological parameters and total ammonia-nitrogen excretion of juvenile striped catfishPangasianodon hypophthalmus

Abstract: A feeding trial was performed to determine the effect of a commercial source of Yucca schidigera and Quillaja saponaria extracts (Nutrafito Plus®), in practical diets, on striped catfish Pangasianodon hypophthalmus growth, feed utilization, body composition, total ammonia‐nitrogen (TAN) excretion and haematological parameters. Four experimental diets were supplemented with Nutrafito Plus® at 0%, 0.01%, 0.02% and 0.03% (diets: control, N01, N02 and N03 respectively). Three replicate groups of striped catfish, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
3
9
1
Order By: Relevance
“…The present study demonstrated that the lowest significant value of TAN and UIA was reported in QS/YS, YS and QS compared with CG. These results correspond with Güroy et al (2016) who found a significant reduction in TAN excretion with 0.3% dietary inclusion of YS and QS extract to the juvenile striped catfish diet, compared to the control. In this context, many studies have focused on the role of YS in mitigating ammonia in aquaculture water with promising findings (Castillo Vargasmachuca et al, 2015;Hassan et al, 2017;Yang et al, 2015;Yu et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrated that the lowest significant value of TAN and UIA was reported in QS/YS, YS and QS compared with CG. These results correspond with Güroy et al (2016) who found a significant reduction in TAN excretion with 0.3% dietary inclusion of YS and QS extract to the juvenile striped catfish diet, compared to the control. In this context, many studies have focused on the role of YS in mitigating ammonia in aquaculture water with promising findings (Castillo Vargasmachuca et al, 2015;Hassan et al, 2017;Yang et al, 2015;Yu et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Dorojan et al (2015) also reported that fish fed diets containing at least 200 mg kg -1 of ginseng herb (Ginsana® G115) for 17 weeks, had enhanced growth performance, feed efficiency, and hematological indices. Similar results concerning the effect of a commercial source of Yucca schidigera and Quillaja saponaria extracts (Nutrafito Plus®), in practical diets, on striped catfish P. hypophthalmus growth, feed utilization, and hematological parameters have also been reported by Guroy et al (2016). .…”
Section: Discussionsupporting
confidence: 72%
“…Güroy et al [20] showed a beneficial impact of a supplementation of juvenile striped catfish (Pangasianodon hypophthalmus) with a mixture of Y. schidigera and Q. saponaria, on the fish growth. Overall, in results obtained in the litterature on the use of saponin-rich plants in aquaculture, an improvement seems to be observed for supplementation doses lower than 1000ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Güroy et al, reported a beneficial impact of a supplementation of juvenile striped catfish (P. hypophthalmus) with a mixture of Y. schidigera and Q. saponaria, on the fish TAN reduction, associated with an improvement in fish growth [20].…”
Section: Discussionmentioning
confidence: 99%